10.1371/journal.pmed.0020297 (CrossRef Listing of Deleted DOIs, 2000)
Infertility poses a multidimensional burden, especially for women in low- and middle-income countries, where it is often associated with social stigma, emotional distress, and limited support. This study aimed to assess the mental health status and its associated factors among women with fertility issues visiting fertility center in the Kathmandu Valley. A cross-sectional study was conducted from October 2023 to April 2024, and participant data collected from November 2023 to February 2024, among 143 women of reproductive age (18-49 years). Nepali versions of the DASS-21 were administered to to collect data. Descriptive and inferential statistics were performed using SPSS version 22.0. The logistic regression model was applied to examine the factors associated with the outcome variable using an adjusted odds ratio with a 95% CI, and a p-value < 0.05 was considered statistically significant. More than four-fifths of respondents (82.5%) reported experiencing some level of anxiety, followed by 51.7% with stress and 35.0% with depression. Women who felt insecure about not having a child had significantly higher odds of stress (AOR = 3.19), while those facing social stigmas also had elevated odds of stress (AOR = 2.91) and anxiety (AOR = 1.55). Experiencing abuse was strongly associated with stress (AOR = 12.76). Women who had never conceived were more likely to experience anxiety (AOR = 2.56), as were those facing financial burdens (AOR = 4.78). Depression was more likely among women dissatisfied with their married life (AOR = 4.30) and among those with a female factor of infertility (AOR = 14.14) compared to unexplained infertility. Increased odds of depression were also associated with longer treatment duration (>5 years) (AOR = 3.34) and higher treatment cost (>5 lakhs) (AOR = 2.71). Anxiety, stress and depression were found to be common among women with fertility issues. Higher psychological distress requires prompt actions to address the mental health needs of women who are battling with infertility.